Antimicrobial susceptibilities of Clostridium difficile. Issue 10 (October 1980) - Shuttleworth, R; Taylor, M; Jones, D M
Abstract : The antimicrobial susceptibilities of 78 strains of Clostridium difficile isolated from patients with and without gastrointestinal symptoms were determined and compared. Strains from patients with symptoms were more likely to show resistance to antibiotics. The antimicrobial susceptibilities of toxigenic and non-toxigenic strains were found to be similar.